4.5 V High‐Voltage Rechargeable Batteries Enabled by the Reduction of Polarization on the Lithium Metal Anode. Issue 43 (27th August 2019) - Yan, Chong; Xu, Rui; Qin, Jin‐Lei; Yuan, Hong; Xiao, Ye; Xu, Lei; Huang, Jia‐Qi
Abstract: Lithium metal is used to achieve high‐energy‐density batteries due to its large theoretical capacity and low negative electrochemical potential. The introduction of quasi‐solid electrolytes simultaneously overcomes the safety problems induced by the liquid electrolytes and the high interfacial resistance issues confronted by all solid‐state electrolytes. In‐depth investigations involving interfacial behaviors in quasi‐solid lithium metal batteries are inadequate. Herein an ultrathin Li3 OCl quasi‐solid‐state electrolyte layer (500 nm thickness) is used to cover a lithium anode. The polarization of the anode is remarkably reduced by introducing the Li3 OCl quasi‐solid‐state electrolyte. In contrast to the decomposition of solvents in a standard electrolyte (EC‐DEC, 1.0 m LiPF6 ), the established quasi‐solid‐state electrolyte interfaces can significantly inhibit the decomposition of solvents when the cut‐off voltage is 4.5 V. Abstract : The interfacial behavior of the quasi‐solid‐state electrolyte layer Li3 OCl was investigated with a three‐electrode setup. An ultrathin Li3 OCl layer can remarkably reduce the over‐potential of the lithium anode and inhibit solvent decomposition, significantly prolonging the service life of a high‐voltage (4.5 V) lithium metal battery.